Partners Taking Turns Leaning In and Leaning Out: Trusting in the Healing Arc of Attachment Dynamics following Betrayal. Issue 3 (3rd July 2022) - Butler, Mark H.; Gossner, Jacob D.; Fife, Stephen T.
Abstract: Betrayal trauma threatens pair-bond attachment relationships. Across a trajectory of repair and healing, offenders and aggrieved partners manifest distinct trajectories, with asynchronous progression and timelines. Without careful intervention, their colliding trajectories may preclude repair and healing, producing instead corrosive interaction and relationship disintegration. We focus on attachment-organized responses designed to safeguard the relationship as partners alternate "leaning in" and "leaning out" of the relationship. We specifically profile the situation of initial offending partner ambivalence. Our attachment-informed model of couple repair and healing following betrayal trauma describes four phases, key developmental tasks, and attachment dynamics related to couples' asynchronous healing trajectories. Although betrayal trauma can lead to relationship dissolution, couples can heal (a) as both partners work together to navigate one partner's "leaning out" with the other partner's "leaning in" responses, (b) as offenders choose to be accountable, witness their partner's pain, and make amends, (c) as aggrieved partners intentionally process the offense through benevolent indignation, and (d) as both address relationship deficits and needs. A clinical vignette depicts the couple experience, and we then discuss the associated relationship dynamics and suggest clinical responses related to each phase.